Coach–Athlete Perceived Congruence Between Actual and Desired Emotions in Karate Competition and Training. Issue 3 (3rd July 2018) - Friesen, Andrew; Lane, Andrew; Galloway, Shaun; Stanley, Damian; Nevill, Alan; Ruiz, Montse C.
Abstract : Coaches can help athletes regulate emotions but would benefit from tools that help them accurately perceive athletes' emotions. In the present study, we investigated the use of video-recorded performances to compare 3 martial artists' ratings of desired and actual emotions with their coach's ratings. Results show how desired emotions progressively fluctuated throughout competition. Furthermore, desired and actual emotions differed between training and performance contexts. Finally, we report correlations between performance and perceived congruence in desired and actual emotions. Cumulatively, results offer support for the video-assisted recall of emotions as an intervention tool in developing emotion regulation abilities.